PV/WT Integrated System Using the Gray Wolf Optimization Technique for Power Quality Improvement - Goud, B. Srikanth; Rami Reddy, Ch.; Naga Sai kalyan, Ch.; Udumula, Ramanjaneya Reddy; Bajaj, Mohit; Abdul Samad, Bdereddin; Shouran, Mokhtar; Kamel, Salah (Frontiers in Energy Research, 2022)
In this paper, Renewable Energy Sources like PV, wind and battery as storing devices are grid integrated using a hybrid shunt active power filter. This integration causes harmonics and imbalances in the system. To mitigate the harmonics and improve the reliability of the system this study suggested the Fractional Order Proportional Integral controller, which works ideally with the aid of Grey Wolf Optimization. With the use of GWO, the parameters of FOPI are tuned which effectively minimizes the harmonics. The proposed system is operated at different load conditions like nonlinear loads and unbalanced loads. The proposed controller has effectively reduced the Total Harmonic Distortions which when compared without filter and with passive filter. The suggested controller is built in the MATLAB Platform and compared to previously established approaches.